AB0015 HLA-G may predict the disease course in patients with early arthritis. (23rd January 2014) - Rizzo, R.; Bortolotti, D.; Farina, I.; Galuppi, E.; Ciancio, G.; Govoni, M.
Abstract : Background: The current strategy to manage early arthritis (EA) and early rheumatoid arthritis (RA) with negative prognostic factors is to start as soon as possible an intensive treatment aimed to reach remission. In the early phases, to avoid under/overtreatment, it is important to identify biomarkers capable of detecting patients at high risk of severe evolution. Several factors have been associated with a severe course [1-4], but their predictive value is still limited [5]. Therefore, additional and reliable markers are needed. HLA-G molecules are nonclassical HLA class I antigens expressed as membrane bound and soluble isoforms (mHLA-G, sHLA-G) with a restricted tissue distribution and anti-inflammatory functions. HLA-G acts as ligand of immune-inhibitory receptors (ILT2, ILT4, KIR2DL4). Expression of HLA-G may be influenced by a 14 bp insertion/deletion polymorphism in exon 8 of the gene, where the deletion is associated with increased mRNA and protein expression [6]. Objectives: sHLA-G levels are positivelycorrelated with RA disease activity [8] and treatment response [8]. We suggest a role both in the immunopathology of the disease and as a useful biomarker to monitor disease course and response to therapy. Methods: We analyzed 14 EA patients attending the Early Arthritis Clinic in our Rheumatology Department during a 12 months follow-up. We evaluated sHLA-G levels in plasma samples by ELISA, mHLA-G and its receptor IL-T2 expression on peripheral blood cells (PBMCs) by flow cytometry. The frequency of HLA-G 14bp polymorphism was evaluated by PCR [9]. Clinical and laboratory parameters, DAS28 and HAQ were checked in each patient along with the pharmacological treatment. Results: The sHLA-G levels inversely correlated with DAS28 parameter during the 12 months follow-up (p<0.0001, Spearman Correlation test). mHLA-G and IL-T2 expression on PBMCs followed the same trend with an increase during the treatment and appearing correlated with the therapeutic response. The distribution of HLA-G polymorphism tends to a correlation between the homozygousity for the deletion and a lower DAS28 (p=0.069, Chi square test). Conclusions: Patients with EA displaying low baseline sHLA-G, mHLA-G and ILT-2 expression suffered a more severe disease. These parameters were inversely correlated with DAS28 variations during the one year follow-up. The genetic HLA-G polymorphism tends to associate the high producer genotype with a lower DAS28. Based on these preliminary results, HLA-G may be a reliable candidate biomarker to evaluate early prognosis, disease activity and inflammation and immune response status in EA patients. More data are needed to evaluate the ability of HLA-G to predict clinical response independently from the therapeutic strategy. References: de Vries-Bouwstra JK, et al. (2008) Arthritis Rheum 58: 1293–98. Raza K, Filer A (2009) Best Pract Res Clin Rheumatol 23: 25–36. Szodoray P, et al. (2010) Autoimmun Rev 9: 140–3. Haupl T, et al. (2010) Ann Rheum Dis 69 Suppl 1: i37–42. Smolen JS, et al. (2008) Arthritis Res Ther 10: 208. Verbruggen LA, et al. (2006) Hum Immunol 67: 561–7. Rizzo R, et al. (2005) Immunogenetics 57: 172-81. Rizzo R, et al. (2006) Pharmacogenet Genomics 16: 615-23. Ongaro A, et al. (2010) Hum Immunol 71: 342-50. Disclosure of Interest: None Declared